(untitled) (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted at the Agronomy Farm, Bangladesh Agricultural University during the aman season of 2005-2006 to investigate the response of different doses of nitrogen application at different growth stages on fine aman rice (cv. kalizira). The experiment consisted of 3 levels of N application namely, 50% of recommended N, 100% of recommended N (150kg ha-1) and 25% higher than recommended N and 3 different plant growth stages of N application namely transplanting, maximum tillering and panicle initiation stage. The application of single super phosphate, muriate of potash, gypsum and zinc sulphate were same in all the plots at the rate of 125, 67, 20 and 5 kg ha-1, respectively. The experiment was laid out in a split plot design (SPD) with three replications. All data were analyzed using the analysis of variance technique and the mean differences were adjusted by DMRT. The results revealed that different doses of nitrogen had significant positive effect on the most of the vegetative parameters. Plant height, numbers of tiller hill-1, leaf hill-1, dry matter hill-1 were to be highest with the increasing rate of nitrogen at all sampling excluding final harvest. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11582 J. Environ. Sci. & Natural Resources, 5(1): 199 - 203, 2012